Association between low dietary zinc and hyperuricaemia in middle-aged and older males in China: a cross-sectional study. Issue 10 (13th October 2015) - Xie, Dong-xing; Xiong, Yi-lin; Zeng, Chao; Wei, Jie; Yang, Tuo; Li, Hui; Wang, Yi-lun; Gao, Shu-guang; Li, Yu-sheng; Lei, Guang-hua
Abstract : Objective: To examine the associations between dietary zinc intake and hyperuricaemia. Design: Cross-sectional study. Setting: This study was conducted in a health examination centre of China. Participants: A total of 5168 middle-aged and older participants (aged 40 years or above) (2697 men and 2471 women) were included. Outcome measures: Dietary zinc intake was assessed using a validated semiquantitative food frequency questionnaire. Hyperuricaemia was defined as uric acid ≥416 µmol/L for males and ≥360 µmol/L for females. Results: For males, the prevalence of hyperuricaemia was 22.9%. After adjusting for age, body mass index (BMI) and energy intake, the ORs were 0.68 (95% CI 0.45 to 0.92) in the second quintile, 0.63 (95% CI 0.45 to 0.89) in the third quintile, 0.68 (95% CI 0.46 to 1.00) in the fourth quintile and 0.55 (95% CI 0.35 to 0.87) in the fifth quintile comparing the lowest quintile of Zn intake, respectively (p for trend=0.03). In the multivariable adjusted model, the relative odds of hyperuricaemia were significantly decreased by 0.71 times in the second quintile of zinc intake (OR 0.71, 95% CI 0.52 to 0.98), 0.64 times in the third quintile (OR 0.65, 95% CI 0.44 to 0.94) and 0.55 times in the fifth quintile (OR 0.56, 95% CI 0.32 to 0.97) compared with those in the lowest quintile, and p for trend was 0.064. For females, the prevalence of hyperuricaemia was 10.0%, and unadjusted, minimally adjusted as well as multivariable adjusted ORs all suggested no significant association between dietary zinc intake and hyperuricaemia. Conclusions: The findings of this cross-sectional study indicated that dietary zinc intake was inversely associated with hyperuricaemia in middle-aged and older males, but not in females. The association was significant after considering the influence of age, BMI and energy intake, and after that, minimum adjustment remained independent of further confounding factors such as vitamin C intake, alcohol drinking status and nutrient supplementation.